Monitoring the crystallization of tartaric acid with THz spectroscopy - Soltani, A.; Gebauer, Denis; Fischer, B.; Colfen, H.; Koch, M. (2017)
© 2017 IEEE. We study the crystallization of L-(+)-Tartaric acid by employing attenuated total reflection THz time-domain spectroscopy (TDS). In the so-called nucleation stage, the absorption spectrum shows a broadband transient increase. Besides, we observed a transient resonance at 750 GHz. This peak can be assigned to aggregation of L-(+)-Tartaric acid molecules including hydrated water molecules. Furthermore, the THz data reveal the vibration of clusters in the solution phase which is confirmed by analytical ultracentrifugation technique.